STEM-PjBL: Its effect on students creative thinking skill in environmental pollution material - Simatupang, Halim; Rangkuti, Yulita Molliq; Saputra, Edi; Rahma, Aulia Eka; Kurniawan, Chandra (Universitas Islam Negeri Sumatera Utara, 2024)
Teaching and learning in the 21st century should equip students with creative thinking skills to be ready to live and contribute productively to society. This study aims to determine the effect of the implementation of STEM-PjBL on Creative Thinking Skill in Environmental Pollution Material of 7-grade. The quasi-experimental design of the nonequivalent pretest-posttest control group was used in this study. The subjects in this study were students of class VII at SMP Negeri 37 Medan. Subject selection was done by purposive sampling technique. The samples of this study consist of class VII-D as the control class and class VII-C as the experimental class. Data collection techniques used in this study were test techniques. The instrument used was the multiple-choice questions consist of 25 questions to measure student learning creative thinking skill based on the Tawil and Liliasari from Building The Knowledge, Arouses Curiosity, Looking at The Different Angle of Information and Forecasting Limited Information. This means that there is an effect for learning between the experimental class and the control class. The average result of the student creative thinking skill in the experimental class was 91% (very good category). The results showed that there was a significant effect of the STEM-PjBL Model on Students Creative Thinking Skill learning was in 0.030 for effect learning with t-test and this is the results of the t-test obtained that the 2-tailed significance value, the STEM-PjBL model can be used as an alternative learning to empower 21st century skills.